2020
DOI: 10.3390/ijms21082787
|View full text |Cite
|
Sign up to set email alerts
|

BST Stimulation Induces Atrophy and Changes in Aerobic Energy Metabolism in Rat Skeletal Muscles—The Biphasic Action of Endogenous Glucocorticoids

Abstract: (1) The primary involvement in stress-induced disturbances in skeletal muscles is assigned to the release of glucocorticoids (GCs). The current study aims to investigate the impact of the biphasic action of the chronic stress response (CSR) induced by the electrical stimulation of the bed nucleus of the stria terminalis (BST) effects on muscle atrophy and aerobic energy metabolism in soleus (SOL) and extensor digitorum longus (EDL) muscles. (2) Male Wistar rats (n = 17) were used. The rats were divided randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Interestingly, in an experiment conducted by Nishida and coworkers, no changes in SOL and EDL muscle mass were observed even during DEX treatment (5 days, dose 600 µg/kg) [ 29 ]. Our recent work [ 25 , 26 ] showed that the CSR and increased CORT level do not have to accompany changes in body and muscle weight (data not shown); nevertheless, an increased level of atrogin-1 was observed. Furthermore, we assume that to explain this phenomenon in these particular conditions, it is necessary to consider intramuscular fat stores in rats from groups exposed to the chronic cold water immersion [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, in an experiment conducted by Nishida and coworkers, no changes in SOL and EDL muscle mass were observed even during DEX treatment (5 days, dose 600 µg/kg) [ 29 ]. Our recent work [ 25 , 26 ] showed that the CSR and increased CORT level do not have to accompany changes in body and muscle weight (data not shown); nevertheless, an increased level of atrogin-1 was observed. Furthermore, we assume that to explain this phenomenon in these particular conditions, it is necessary to consider intramuscular fat stores in rats from groups exposed to the chronic cold water immersion [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 91%
“…Our results indicate that DEX-induced muscle loss is abolished in rats supplemented with vitamin D 3 but only in SOL muscle. Based on previously published data [ 25 ], we assumed that a similar effect should be observed in the CSR conditions. However, instead of HPA axis activation and CORT surge, we did not note any changes in the body and muscle weight.…”
Section: Discussionmentioning
confidence: 96%
“…Irisin is a novel myokine and adipokine in various body tissues, including skeletal muscle, myocardium and adipose tissue, which can be effectively induced by several kinds of stimulation such as exercise training [ 9 , 14 ]. Some research showed that many different types of exercise can significantly increase the myocardial Irisin expression [ 26 , 27 , 28 , 29 ]. This study found that the expression of myocardium irisin/FNDC5 was significantly up-regulated in different exercise intervention and skeletal muscle electrical stimulation models, among which the resistance exercise had the significant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GC signalling through the GR is a trigger of insulin resistance in muscles, supressing GLUT 4 translocation to the cell surface, as well as downregulating glycogen synthesis [ 66 ]. It would appear that the GR interacts directly with both the insulin and insulin-like growth factor 1 (IGF-1) pathways [ 67 ], although detailed mechanistic studies of GC effects in muscle carbohydrate metabolism are severely lacking [ 3 ].…”
Section: The Physiological Response To External Psychosocial Stresmentioning
confidence: 99%